Strengthening Palliative Care Systems in Indonesia: A Strategic Policy Brief to Address Health System Gaps - Agustina, Rismia; Romadhon, Pradana Zaky; Lin, Mei- Feng (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Cancer is one of the most burdensome diseases in Indonesia, ranking as the second-highest cost contributor in the National Health Insurance (Jaminan Kesehatan Nasional) scheme, with expenditures reaching 3.2 trillion rupiahs (approximately 221 million USD). Palliative care is an essential component of cancer management, aimed at alleviating physical, emotional, and psychosocial suffering. However, access to palliative care in Indonesia is extremely limited, with services available in only seven hospitals across three major islands, leaving most regions underserved. Objective: This policy brief aimed to analyze existing challenges and propose strategic policy recommendations for strengthening palliative care services to address healthcare system pressures in Indonesia, particularly related to cancer. Methods: A narrative policy analysis was conducted using secondary data from national healthcare reports, cost analyses, and peer-reviewed literature on palliative care effectiveness. The review assessed service coverage, accessibility, financial burden, and policy frameworks to identify key gaps and opportunities. Results: The analysis highlighted critical disparities in access to palliative care across Indonesia’s geographically dispersed regions. Despite evidence supporting the cost-saving and quality-of-life benefits of palliative services, implementation remains centralized and fragmented. Lack of national integration, workforce capacity, and public awareness were identified as major barriers. Conclusion: Developing an integrated, nationwide palliative care strategy is urgently needed to mitigate healthcare costs and improve quality of life for patients with cancer and other life-limiting illnesses. Policy efforts should focus on decentralizing services, expanding training for health professionals, and incorporating palliative care into primary healthcare systems.